Analysis of the opportunities of social inclusion of children from families at social risk in communities - Alifanovienė, Daiva; Šapelytė, Odeta; Bėčiūtė, Nomeda (Social Welfare: Interdisciplinary Approach, 2016)
The article deals with the opportunities of social inclusion of children from families at social risk attending children’s day care centres into community life, social educational and cultural activity, volunteering. The article presents the analysis of a qualitative semi-structured interview. Performing target content analysis of the experiences of the professionals of children’s day care centres (N=10) the main directions of social inclusion of the members of families at risk and their realization opportunities from the aspect of the subjective opinion of the professionals revealing current situation and predicting possible demands are emphasized